Montoneros or the white whale: Malvinas as the intersection of two utopical obsessions - Svetliza, Exequiel (Diablotexto Digital, 2022)
The Malvina’s war is an historic episode involving deep social, political and ideological contradictions. Montoneros o la ballena blanca (2012), a novel by Federico Lorenz, dig into the convulsed world of the political violence in Argentina during the 70’s and 80’s, to represent two wars: the internal war, between the left wing and the AAA (Argentine Anti-communist Alliance); and the external war, between Argentina and the United Kingdom over the South Atlantic Islands. The novel merges history and fiction to reveal an obsession shared by the left and right Argentinian political wings: Malvinas. La guerra de Malvinas es un episodio histórico atravesado por profundas contradicciones sociales, políticas e ideológicas. Montoneros o la ballena blanca (2012), la novela del historiador Federico Lorenz, ingresa en el convulsionado mundo de la violencia política argentina de las décadas del 70 y 80 para representar dos guerras: la interna, entre la izquierda revolucionaria y la triple A (Alianza Anticomunista Argentina); y la externa, entre Argentina y Gran Bretaña por las islas del Atlántico sur. Historia y ficción se entremezclan en el texto para develar la compartida obsesión de la izquierda y la derecha argentina por Malvinas.